2016
DOI: 10.4314/gmj.v50i2.5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between serum total magnesium and serum potassium in emergency surgical patients in a tertiary hospital in Ghana

Abstract: SUMMARYIntroduction: Potassium and magnesium are the two most abundant intra-cellular cations. They play pivotal roles in many essential biological processes. Deficiencies of these electrolytes are of clinical importance in hospitalised patients. Aim: To determine the relationship between serum total magnesium and potassium levels in adult patients requiring an emergency intra-abdominal surgery and the clinical utility of this relationship in the care of patients. Methods: A cross sectional study was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
(20 reference statements)
1
6
0
Order By: Relevance
“…(13) Similar findings of frequent association between hypokalemia and hypomagnesemia were reported in previous studies. [5,6] Furthermore, in support of the results of this study concomitant Mg deficiency in K-depleted patients ranged from 38% to 42%., which was demonstrated by Whang et al [7] reported that 42% of patients on admission with hypokalemia also have concomitant hypomagnesemia. However, the findings of Deheinzelin et al [9] and Watson and O'Kell.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…(13) Similar findings of frequent association between hypokalemia and hypomagnesemia were reported in previous studies. [5,6] Furthermore, in support of the results of this study concomitant Mg deficiency in K-depleted patients ranged from 38% to 42%., which was demonstrated by Whang et al [7] reported that 42% of patients on admission with hypokalemia also have concomitant hypomagnesemia. However, the findings of Deheinzelin et al [9] and Watson and O'Kell.…”
Section: Discussionsupporting
confidence: 82%
“…Hypokalemia has been found to be frequently associated with hypomagnesemia in hospitalized patients according to previous reports mainly from studies done among Caucasians. (5)(6)(7)(8)(9) Magnesium deficiency, when present, worsens hypokalemia by aggravating renal wasting of potassium and enhances the adverse effects of hypokalemia. Because both hypokalemia and hypomagnesemia can be induced by the same mechanisms (e.g., diuretic administration, primary hyperaldosteronism, renal tubular acidosis) attention in recent years has been focused on their co-occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…The Proposed method simplifies the body temperature and the white blood cell count as nonsignificant variables, which are identified as nonzero but with a very small effect using the CC method. It is also worthwhile to mention that the Proposed method signifies the magnesium level with a quite significant coefficient, which was extensively investigated in the scientific literature [33][34][35].…”
Section: Real Data Applicationmentioning
confidence: 99%
“…Total serum magnesium measurements may actually overestimate the incidence of hypomagnesemia when hypoalbuminemia is present and thus serum ionized magnesium may better estimate magnesium levels [17]. Contradictory to this, subsequent studies have not found these relationships to be valid [18][19][20][21]. Further studies understanding whether magnesium levels fluctuate with albumin levels are needed.…”
Section: Importance Of Magnesiummentioning
confidence: 99%